Resolution-dependent performance of grounding line motion in a shallow model compared with a full-Stokes model according to the MISMIP3d intercomparison. Issue 220 (2014) - Feldmann, J.; Albrecht, T.; Khroulev, C.; Pattyn, F.; Levermann, A.
Abstract: Making confident statements about the evolution of an ice-sheet–shelf system with a numerical model requires the capability to reproduce the migration of the grounding line. Here we show that the shallow-ice approximation/shallow-shelf approximation hybrid-type Parallel Ice Sheet Model (PISM), with its recent improvements, is capable of modeling the grounding line motion in a perturbed ice-sheet–shelf system. The model is set up according to the three-dimensional Marine Ice-Sheet Model Intercomparison Project (MISMIP3d), and simulations are carried out across a broad range of spatial resolutions. Using (1) a linear interpolation of the grounding line with locally interpolated basal friction and (2) an improved driving-stress computation across the grounding line, the reversibility of the grounding line (i.e. its retreat after an advance forced by a local perturbation of basal resistance) is captured by the model even at medium and low resolutions (∆ x > 10 km). The transient model response is qualitatively similar to that of higher-order models but reveals a higher initial sensitivity to perturbations on very short timescales. Our findings support the application of PISM to the Antarctic ice sheet from regional up to continental scales and on relatively low spatial resolutions.